Pattern of Common Inherited Coagulation Disorders: Evaluation of 100 Cases (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The bleeding disorders having inherited abnormality of haemostasis may present with significant difficulties in diagnosis and management. The overall frequency of these disorders in the general population is low.Objectives: To study the frequency of inherited coagulation disorders and their prevalent clinical manifestations.Materials and Methods: A prospective cross sectional study of one hundred patients of all age group and both sexes was organized as both in-patient and out-patient based in the Department of haematology, Armed Forces Institute of Pathology (AFIP) from July 2012 to June 2013.Results: In this study, out of 100 patients, haemophilia A, diagnosed in 75% patients, was the most common disorder. Age group ranging from 5-15 years constituted 48% of total patients. Male to female ratio of patients having hereditary coagulation defect was 73:2 in haemophilia A whereas 2:3 in vWD. Consanguinity was documented in 60% of vWD and 24% of haemophilia A. The most common clinical symptom in hereditary coagulation defect (HCD) was echymosis (60%). The most common presenting feature of haemophilia was haematoma (57.95%) whereas menorrhagia was the most common presentation of female patients with vWD. Among 97 patients of haemophilia and vWD, 59(60.82%) cases were in mild form and 04(4.12%) cases were found to have severe coagulation defect. Fresh frozen plasma (FFP) is the most common modality of treatment in HCD.Conclusion: It has become the need of the time to find out such a cost effective diagnostic parameter to make an early diagnosis of inherited coagulation disorders.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 64-66